Role of coopetition in development of golf course business models - Koivu, Karri (2018)
Conservative game of golf is facing growing number of demands from increasingly competitive and developed markets. Trends suggest the competitiveness of the market growing with more sensitive customers demanding increasing flexibility of offerings. Traditional golf courses business models have not been designed for the demanded flexibility thus the study aims to shed light into the ability of golf courses to cope with changing demands in terms of their business models. Moreover, the study aims to evaluate the role of coopetition in the business model development of golf operators. This study uses qualitative multiple case study to inspect the market perceptions, business model development and the role of coopetition in business models of five golf courses that were chosen to offer variety of perspectives for the research. Extensive and interpretive approach on data collection and its analysis provides insightful developments on the underresearched field of golf business. The findings point towards market dynamics being perceived as thrust to develop golf courses towards larger multi course structures. Moreover, a favourable view on commercially oriented rather than member-owned golf courses regarding the capabilities of business model development and innovations. Finally, the study illustrates the benefits that larger golf course establishments may be able to achieve but does not confirm the pursue of all these benefits being possible via coopetitive actions and partners. Role of coopetition in the golf course business model development is supported although it may not be suitable for all types of golf course. Therefore, the study leaves room for further research to be carried out on coopetition and its ability to enhance the business model development of golf courses.